Parallel programming of exogenous and endogenous components in the antisaccade task. - Massen, Cristina (Quarterly Journal of Experimental Psychology: Section A, 2004)
A study was conducted to investigate the inhibitory mechanisms responsible for successful performance in the antisaccade task, where subjects are required to suppress the reflexive tendency to look at a peripherally presented stimulus and to perform a saccade in the opposite direction instead. Findings revealed support for a hypothesis of parallel programming of exogenous and endogenous components, where a reflexive saccade to the stimulus is automatically programmed and competes with the concurrently established voluntary program to look in the opposite direction.